2019
DOI: 10.1111/cup.13484
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of primary cilium in acral melanoma

Abstract: Background A eukaryotic cell's primary cilium (PC) is critical for cell signaling, migration and homeostasis. Primary cilium dysfunction has been demonstrated in several malignancies, but whether primary cilia loss occurs in acral melanoma has remained unknown. To address this, we examined the ciliation index (% melanocytes containing a PC) of patient‐derived, biopsy‐proven acral melanoma and compared these to benign acral nevi. Methods We generated a pilot initiative study that included six acral melanomas an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…Though there are a variety of diagnostic tools available to aid in achieving the most accurate assessment of malignancy [11,12], diagnostic uncertainty can persist in ambiguous lesions. Multiple studies have now demonstrated that primary cilia are lost in melanoma and retained in nevi [13][14][15][16][17]. These studies suggest the potential for using primary cilia staining as an adjunct diagnostic tool for dermatopathologists.…”
Section: Introductionmentioning
confidence: 94%
“…Though there are a variety of diagnostic tools available to aid in achieving the most accurate assessment of malignancy [11,12], diagnostic uncertainty can persist in ambiguous lesions. Multiple studies have now demonstrated that primary cilia are lost in melanoma and retained in nevi [13][14][15][16][17]. These studies suggest the potential for using primary cilia staining as an adjunct diagnostic tool for dermatopathologists.…”
Section: Introductionmentioning
confidence: 94%
“…Primary cilia are cell-surface organelles that are lost in unambiguous cases of melanoma and retained in conventional melanocytic nevi, which has led to the introduction of the Ciliation Index (CI) as a molecular means of distinguishing these groups of melanocytic lesions (Kim et al, 2011;Lang et al, 2020;Love et al, 2019;Snedecor et al, 2015). The distinctive morphology of primary cilia makes them easily identifiable on the surface of melanocytes using immunofluorescence labeling with antibodies specific to the basal body (internal portion) and ciliary axoneme (external portion) (Kim et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The same authors performed similar analyses on a series of 10 cases of primary invasive melanoma arising in association with a nevus and found a significant reduction of primary cilia in the cells comprising invasive melanoma (4% AE 7%) from its paired associated nevus (59% AE 17%) (Lang et al, 2020a). Finally, the same authors showed that acral melanomas exhibited a reduced CI (9.3% AE 7%) compared with acral nevi (74% AE 3%) (Love et al, 2019) and, further, that progressive loss of ciliation occurred with increasing severity of dysplasia (55% AE 22% in mild compared with 14% AE 12% in severe dysplastic nevi) (Lang et al, 2016). These studies prompted the work reported by Lang et al (2020b).…”
mentioning
confidence: 76%
“…Because melanocytes in melanoma typically proliferate at a higher rate than melanocytes in a benign nevus, and because the microtubule apparatus is intricately related to cell division, one explanation for the observed reduction of CI in melanoma might be related to increased proliferation index in melanoma. However, CI does not correlate with the Ki-67 proliferation index (Kim et al, 2011;Love et al, 2019). As such, the processes driving loss of primary cilia in melanoma are likely multifactorial and require further investigation.…”
Section: Sm)mentioning
confidence: 96%